Role of industrial training institutes in the development of human resources in industry / Rashid Esoofi Mamajiwalla - Mamajiwalla, Rashid Esoofi (1992)
One of the most important resources available to an organization, and many would say the most important, is its employees. Their competence, experience and loyalty largely determine both the objectives that an enterprise can set for itself and how successful it will be in achieving them. This fact of industrial and commercial life is not new but, since the last war, economic, technological and social changes have forced employers to pay particular attention to their manpower policies and practices. The rapid evolution of personnel management as a major business function is itself a direct result of the growing managerial concern for the more effective use and development of human resources. Within the framework of organizational goals, the goals of training become quite specific. Training is one management tool used to develop the full effectiveness of an essential organizational resource: its people. The function of training, then, is to bring about the behaviour changes required to meet management's goals. When considered from the point of view of a system's overall mission, a training function is no longer an extra operation within the organization; it is an essential subsystem used to fulfil the larger system's specific mission.